Construction of an Electron Transfer Mediator Pathway for Bioelectrosynthesis by Escherichia coli - Feng, Jiao; Lu, Qiuhao; Li, Kang; Xu, Sheng; Wang, Xin; Chen, Kequan; Ouyang, Pingkai (Frontiers in Bioengineering and Biotechnology, 2020)
Microbial electrosynthesis or electro-fermentation is a promising microbial electrochemical technology for the synthesis of valuable chemicals or high-value fuels with aid of microbial cells as catalysts. By introducing electrical energy (current), fermentation environments can be altered or controlled in which the microbial cells are affected. The key role for electrical energy is to supply electrons to microbial metabolism. To realize electricity utility, a process termed inward extracellular electron transfer (EET) is necessary, and its efficiency is crucial to bioelectrochemical systems. The use of electron mediators was one of the main ways to realize electron transfer and improve EET efficiency. To break through some limitation of exogenous electron mediators, we introduced the phenazine-1-carboxylic acid (PCA) pathway from Pseudomonas aeruginosa PAO1 into E. coli. The engineered E. coli facilitated reduction of fumarate by using PCA as endogenous electron mediator driven by electricity. Furthermore, the heterologously-expressed PCA pathway in E. coli led to better EET efficiency and a strong metabolic shift to greater production of reduced metabolites, but lower biomass in the system. Then, we found that synthesis of adenosine triphosphate, as the “energy currency” in metabolism, was also affected. The reduction of menaquinon was demonstrated as one of the key reactions in self-excreted PCA-mediated succinate electrosynthesis. This study demonstrates the feasibility of electron transfer between the electrode and E. coli cells using heterologous self-excreted PCA as an electron transfer mediator in a bioelectrochemical system and lays a foundation for subsequent optimization.